PROCESSING OF EDUCATION ASSESSMENT RESULTS IN THE EVALUATION OF LEARNING OUTCOMES - Adiyono Adiyono; Herla Astuti (Salwatuna, 2022)
Abstract This study discusses how the results of educational assessments become a benchmark in determining student achievement. Giving a score is a result of an answer that can be converted into a number on the score. and the score obtained from a question that is answered by students correctly and can consider the weight of the answer. The main focus that we will discuss is the processing of educational assessment results. The purpose of this study was to determine the processing of educational assessment results. So that education can be used as a reference in processing student learning outcomes. Analyze how the processing of the assessment results in the learning process. Based on this goal, scoring is very important in learning, especially for students.